Eat Your Heart Out - deVos, Kelly (New York : Razorbill, 2021)
Six disgruntled teens are forced to spend their winter break at fat camp during Flagstaff, Arizona's worst blizzard in a century, only to find that Camp Featherlite is even worse than expected because it is crawling with genetically-modified monsters.
Ages 12 and up.
Keywords: Horror stories; Overweight persons -- Fiction; Survival -- Fiction; Genetic engineering -- Fiction; Camps -- Fiction